Single and Synergistic Effects of Fenbendazole and Metronidazole Against Subclinical Infection by Giardia duodenalis in Non-Human Primates in a Zoological Garden in Southern Italy - Capasso, Michele; Ciuca, Lavinia; Procesi, Isabel Guadano; Zinno, Francesco; Berrilli, Federica; Cringoli, Giuseppe; Rinaldi, Laura (Frontiers in Veterinary Science, 2022)
The aim of this study was to assess the single and synergistic effects of fenbendazole (Fenb) and metronidazole (Metro) for the treatment of Giardia duodenalis infection in different species of non human primates (NHP) housed in a zoological garden of southern Italy. Moreover, the study also aimed to better define the circulation of G. duodenalis zoonotic assemblages in NHP and the potential occurrence of zoonotic transmission between the staff from the zoo and NHP. Briefly, six species belonging to four families (Lemuridae, Cercopithecidae, Atelidae, Hylobatidae) of NHP and housed in six cages (CG) were identified as Giardia-positive, and divided in two groups. Group F (N=16 animals) was treated with Fenb (50 mg/kg, every 24 hours for 5 consecutive days) and Group M (N=7 animals) was treated with Metro (25 mg/kg, twice a day for 5 consecutive days). After the first round of therapy, all the animals were retreated for five days by inverting the drugs in each group. At each sampling day (SDs -3-24) the samples were tested for the presence of Giardia cysts using the FLOTAC technique. Multiple faecal tests for the antigen-detection of Giardia such as rapid ELISA and direct immunofluorescence (IFA) were performed at each sampling point only on samples that resulted positive for Giardia cysts with FLOTAC. The efficacy of Fenb ranged from 30 to 67% and for Metro ranged between 82-96%. The results showed the synergistic effects of Metro and Fenb (98-100%) over the combination of fenbendazole and metronidazole (52-90%) against the infection by Giardia in NHPs. The overall k agreement between FLOTAC and IFA reached 0.858 (P=0.0001). In contrast, all the samples had a negative antigen result when using ELISA. At molecular analysis, six samples were confirmed positive for Giardia by nested PCR. Only two positive samples were successful sequenced showing 100% of identity with Assemblage B. All the samples from the humans included in the study resulted negative for Giardia cysts. Overall, the study emphasizes the need for regular monitoring of Giardia infections in NHP housed in zoos by traditional diagnostic tools combined with molecular characterization of the parasite.